Two Community Nutrition Projects in Africa : Interim Findings - Marek, Tonia (World Bank, Washington, DC, 2012)
The Madagascar Food Security and Nutrition Project (SECALINE) and the Senegal Community Nutrition Project (CNP) were designed to prevent malnutrition and to diminish existing malnutrition rates among children under three years old. The former has been in implementation since July 1993 and the latter since mid-December 1995. Both projects have many similarities, due in part to strong political involvement, effective local commitment, very able and dedicated national staff, and in part to the fact that the same Bank staff helped to design them. Also, lessons learned from other nutrition projects have been fed into the dsin of these two projects. However, these two projects also differ in many respects. Analyzing these projects might therefore be useful for other countries which will like to diminish malnutrition rates through a completely preventive approach using non-governmental delivery mechanisms.